MEMBANGUN KETAHANAN KELUARGA MELALUI BIMBINGAN PERNIKAHAN BAGI REMAJA USIA NIKAH DI DUSUN PRINGWULUNG DESA BENDUNGANJATI KECAMATAN PACET KABUPATEN MOJOKERTO - Nashrun Jauhari; Ratna Suraiya; Intan Wulandari (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Family resilience as a potential family situation in realizing the welfare of life. This discourse needs to be introduced to teenagers of marriageable age to form their identity as potential family subjects. This community service focuses on efforts to build family resilience through marriage guidance for groups of married-age teenagers who live in a rural village where household problems often occur. This community service uses a Problem based Service Learning method model with an effort to provide problem solving to community partners. The conclusive results of this service show that: (1) marriage guidance for adolescents of marriageable age is a relevant effort to form identity in building family resilience; (2) marriage guidance through socialization of the Marriage Law with religious teachings that are more easily absorbed by rural communities of the religious type; (3) the provision of marriage guidance activities with collaboration between service learning actors and community partners is better able to increase community participation